Pembangunan Aplikasi Pengenalan Kanker Melanoma berbasis Android - Abdurrahman Diewa Prakarsa; Komang Candra Brata; Hurriyatul Fitriyah (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Cancer is a disease caused by the uncontrolled growth of abnormal cells in the human body. Melanoma cancer or also known as mole cancer which is included in skin cancer is one of the rare cancers and is one of the most virulent cancers because it can easily spread to organs. Of course the ideal thing that is expected is not to fall sick, but it is better if we have knowledge about melanoma cancer in order to avoid melanoma cancer. The author sees an opportunity to make an application about melanoma cancer based on Android that can introduce and provide general knowledge in a general form so that it encourages users to come to the doctor for a checkup when their mole is not properly shaped. The author will build an application that has features that will be adapted to the needs and will be implemented using the Java programming language. Tests on the application are carried out using functional testing, detection testing, and usability testing methods. In functional testing using blackbox and getting 100% valid results because it has fulfilled all the needs. The accuracy test got 56% accuracy and usability test using SUS (System Usability Scale) got a SUS score of 78 with good information..